Forecasting New Events Occurrence Time on The Example of the Analysis of Foresight Research Results - Poradowska, Konstancja (Prognozowanie czasu zajścia nowych zdarzeń na przykładzie analizy wyników badania foresight, 2010)
The basic tools in the new events forecasting are the methods based on judgmental knowledge of the group of the qualified experts. The group of the qualified experts is usually not enough big and therefore it is groundless to use classical statistical tools. Instead it is common to utilize some subjective probability distribution for statistical interference. In previous papers to describe the subjective probability distribution I have applied triangular, two-sided-power, beta, Weibull's distributions and in case of one person opinion analysis - trapezoidal and uniform distributions. In this paper I have additionally shown a method of new events forecasting for foresight research outputs analysis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 113-124
Keywords: judgmental forecasting; subjective probability; Delphi method; foresight